A Pooled Analysis of Three Randomized Phase I/IIa Clinical Trials Confirms Absence of a Clinically Relevant Effect on the QTc Interval by Umibecestat. Issue 6 (23rd July 2020) - Vormfelde, Stefan Viktor; Pezous, Nicole; Lefèvre, Gilbert; Kolly, Carine; Neumann, Ulf; Jordaan, Pierre; Ufer, Mike; Legangneux, Eric
Abstract : Umibecestat, an orally active β‐secretase inhibitor, reduces the production of amyloid beta‐peptide that accumulates in the brain of patients with Alzheimer's disease. The echocardiogram effects of umibecestat, on QTcF (Fridericia‐corrected QT), on PR and QRS and heart rate (HR), were estimated by concentration‐effect modeling. Three phase I/II studies with durations up to 3 months, with 372 healthy subjects over a wide age range, including both sexes and 2 ethnicities, were pooled, providing a large data set with good statistical power. No clinically relevant effect on QTcF, PR interval, QRS duration, or HR were observed up to supratherapeutic doses. The upper bound of 90% confidence intervals of the ∆QTcF was below the 10 ms threshold of regulatory concern for all concentrations measured. Prespecified sensitivity analysis confirmed the results in both sexes, in those over and below 60 years, and in Japanese subjects. All conclusions were endorsed by the US Food and Drug Administration (FDA).